International governmental agencies and career guidance - Conger, Stuart (Orientación y Sociedad.)
The international Organization for Economic Cooperation and Develop-ment (OECD), like many national and international organizations concerned with economic development believes that career guidance has an important role in promoting the development of a country's human resources. (Mapping the future: Young People and career guidance OECD, 1996). Generally the economic development agencies always recommend that career guidance services should be strengthened. Too frequently, however, they do not recognize the difficulties facing counselor in the schools and do not give clear and specific recommendations, yet they appear to believe that the education or other au thorities who are responsible to guidance will quickly agree and provide more resources for guidance. In addition to economic development agencies, social and educational development agencies also make important recommendations concerning the provision of guidance services. UNESCO, for example, has published two re- cent reports (Policies and Guidelines for Educational and Vocational Guidelines for Equal Access and Opportunity for Girls and Women in Technical and Vocational Education.) It is interesting to compare the OECD and UNESCO rec- ommendations and note that the relative strengths of each set of recommenda- tions, and to imagine how they might be combined in advocating changes in policies and programs.